Strengthening Adolescent Mental Health Support in Schools: A Study on Strategies and Implementation - Fanesa Maura Aprillia (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
This study explores adolescent mental health in schools with a focus on existing prevention and intervention strategies. The background of this research is driven by the increasing prevalence of mental health issues among students and the limitations of the effectiveness of current programs. The main issue is how the strategies implemented can effectively address students' mental health needs. The aim of this research is to assess the effectiveness of various school mental health programs and identify challenges and solutions to improve their implementation. The research methods include an in-depth literature review of various studies and reports on mental health strategies. The findings indicate that although many strategies have been implemented, their effectiveness is often hindered by resource limitations and stigma. The main conclusion is the need for a more integrated and data-driven approach to enhance mental health support in schools, actively involving all stakeholders.